Rekonstruksi Strategi Internasionalisasi Perguruan Tinggi: Sebuah Tinjauan Reflektif - Ambar Sari Dewi (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Globalization have encouraged higher education institutions to undertake internationalization. However, its implementation still faces challenges at the academic, governance, and facilities and infrastructure levels. This study aims to investigate internationalization at the State-owned Islamic Higher Education Institution (PTKIN), specifically at the Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta. Using a descriptive quantitative approach, this study analyzes the relationship between internationalisation strategy and dimensions to internationalisation programs and activities in the university studied. Data were collected through a survey to university and faculty leaders, study program managers, and educational staff. The results show a positive and significant relationship between internationalization strategies and dimensions with internationalization. Other findings demonstrate the consistency of internationalization efforts at UIN Sunan Kalijaga in terms of HEIs governance, academics, research, and student affairs. In addition, this study identified three challenges faced by UIN Sunan Kalijaga as a consequence of changes in internationalization priorities at UIN Sunan Kalijaga, namely budget availability, staff/lecturer competence, and facilities/infrastructure supporting internationalization.This study suggests four recommendations, namely collaboration between institutions, establishment of international classes, provision of supporting facilities and infrastructure, enhancement of the number and amount of budgets for international publication/research, and improvement capacity for lecturers/staff.